Penerapan Value Engineering Pekerjaan Balok, Kolom Dan Pelat Lantai (Studi Kasus: Gedung Perpustakaan Daerah Kabupaten Bengkalis) - Natalia, Monika; Mirani, Zulfira; Syahputra, Jufrinal (MEDIA KOMUNIKASI TEKNIK SIPIL, 2022)
Cost construction must be planned efficiently and optimally. Value Engineering is planned approach with the aim of identifying and streamlining unnecessary costs with functional limitations and work quality (Firda, 2018). In reality, structural work using concrete estimated to over design, overcost (Apriani, 2020). This research was Bengkalis Public Library project. This building consists of 3 floors with an area of 2250 m2. The structure of beams, columns and slabs reinforced concrete. Dimensions of column 40x40 cm, main beam dimensions 40x60 cm, joist beam dimensions 25x40 cm, roof beam dimensions 30x50 cm, and slabs 15 cm with D10-100. Cost of reinforced concrete Rp. 4.297.170.000,00. In value engineering, the conversion of reinforced concrete to profile steel, cost of profile steel Rp. 4.089.619.000,00. it is obtained that the column uses WF 250.250.11.11, WF 400.200.7.11 main beam, WF 200.150.6.9 joist beam and WF 250.125.6.9 roof beam and floor slabs are converted to flourdack plate using 0.75 thickness bondack mm with wiremesh reinforcement M10-150. Cost ratio reinforced concrete and steel profiles is Rp. 207,551,000, -. Steel profiles is 5.075% cheaper than reinforced concrete structures.